STUDYING THE CAPABILITIES OF A COMPLEX OF GEOPHYSICAL METHODS IN THE CHARMITAN GOLD DEPOSIT (Conference Zone, 2022)
An increase in the depth of mining at the Charmitanovskoye vein deposit complicates the geomechanical situation, which is expressed in an increase in the number of collapses of host rocks in the treatment area, where the workers of the treatment plant are located. The only way to normalize the geomechanical environment is to introduce development systems with goaf backfilling. In connection with the above, full-scale methods for measuring the stress state by the finite element method and modeling the geomechanical situation were carried out. In the course of the research, the parameters of force fields in natural and technogenically altered areas of the field were evaluated and safe design parameters of development systems were substantiated. This article is about studying the possibilities of integrated geophysical methods at the Charmitan gold deposit